Nanostructured semiconductor solar absorbers with near 100% absorption and related light management picture. (3rd May 2016) - Li, Yali; Gao, Pingqi; Chen, Qiang; Yang, Jiaming; Li, Junshuai; He, Deyan
Abstract: Optical behaviors of both polycrystalline silicon (Si) and gallium arsenide (GaAs) nanocone (NC)-capped nanowire (NW) arrays are systematically investigated and a full light management picture is presented. The study demonstrates that compared to shape- and environment-sensitive optical resonance modes, including leaky modes and guided longitudinal resonances, optimization of light harvesting based on light scattering is more operable to guide related device fabrication. Under this consideration, near 100% absorption above the bandgap energy is realized for GaAs NC-capped NW arrays with an effective thickness of only 1000 nm through balancing antireflection and light scattering in the optical systems. Further study under oblique incidence shows that light absorption for the optimized NC-capped NW arrays is almost insensitive to the incident angle, indicating excellent omnidirectional light management in the NC-capped NW configuration.